Compensatory movement strategies differentially affect attention allocation and gait parameters in persons with Parkinson’s disease - Yogev-Seligmann, Galit; Krasovsky, Tal; Kafri, Michal (Frontiers in Human Neuroscience, 2022)
Persons with Parkinson disease (PwP) are advised to use compensatory strategies such as external cues or cognitive movement strategies to overcome gait disturbances. It is suggested that external cues involve the processing of sensory stimulation, while cognitive-movement strategies use attention allocation. This study aimed to compare over time changes in attention allocation in PwP between prolonged walking with cognitive movement strategy and external cues; to compare the effect of cognitive movement strategies and external cues on gait parameters; and evaluate whether these changes depend on cognitive function. Eleven PwP participated in a single-group pilot study. Participants walked for 10 minutes under each of three conditions: natural walking, using external cuing, using a cognitive movement strategy. Attention and gait variables were extracted from a single-channel electroencephalogram and accelerometers recordings, respectively. Attention allocation was assessed by the % of Brain Engagement Index (BEI) signals within an attentive engagement range. Cognitive function was assessed using a neuropsychological battery. The walk was divided into two-minute time segments, and the results from each two-minute segment were used to determine the effects of time and condition. Associations between cognitive function and BEI signals were tested. Findings show that in the cognitive movement strategy condition, there was a reduction in the % of BEI signals within the attentive engagement range after the first two minutes of walking. Despite this reduction the BEI did not consistently differ from natural and metronome walking. Spatiotemporal gait variables were better in the cognitive movement strategy condition relative to the other conditions. Global cognitive and information processing scores were significantly associated with the BEI only when the cognitive movement strategy was applied. In conclusion, the study shows that a cognitive movement strategy has positive effects on walking variables but may impose a higher attentional load. Furthermore, when walking using a cognitive movement strategy, persons with higher cognitive function showed elevated attentive engagement. The findings support the idea that cognitive and attentional resources are required for cognitive movement strategies in PwP. Additionally, this study provides support for using single-channel EEG to explore mechanistic aspects of clinical interventions.